Comparison of Three Endodontic Irrigant Regimens against Dual-Species Interkingdom Biofilms: Considerations for Maintaining the Status Quo - Om Alkhir Alshanta (Antibiotics, 2020)
Endodontic infections are often interkingdom biofilms, though current clinical management rarely considers this phenomenon. This study aimed to evaluate new and standard endodontic antimicrobial regimens against simple and complex Candida albicans and Enterococcus faecalis mono- and dual-species biofilms. C. albicans and E. faecalis mono- and dual-species biofilms were grown upon Thermanox™ coverslips and treated for 5 min with 3% NaOCl, 3% NaOCl followed by 17% EDTA, or 9% HEDP dissolved in 3% NaOCl. The number of cells remaining immediately after treatment at 0 h and after 72 h of regrowth were assessed using real-time quantitative PCR. All three treatment arms showed a similar positive antimicrobial effect on C. albicans and E. faecalis in both mono- and dual-species biofilms following initial treatment, resulting in ≥98% reduction in colony forming equivalent (CFE). Regardless of species or biofilm type (mono- or dual- species), the antimicrobial effect of NaOCl:HEDP mixture was comparable to that of NaOCl alone, with both showing significant regrowth after 72 h, whereas sequential treatment with NaOCl and EDTA consistently prevented significant regrowth. Our data suggest that sequential irrigation with NaOCl and EDTA remains the antimicrobial strategy of choice as it significantly reduces biofilm persistence and regrowth in our experimental dual-species biofilm conditions.